A mid-Cretaceous change from fast to slow exhumation of the western Chinese Altai mountains: A climate driven exhumation signal?. (1st August 2020) - Pullen, Alex; Banaszynski, Matthew; Kapp, Paul; Thomson, Stuart N.; Cai, Fulong
Graphical abstract: Highlights: New apatite fission track ages for N  = 6 samples range from 68 to 104 Ma. Apatite U-Th-Sm/He dates range from 56 to 272 Ma for N  = 23 samples. Inverse modeling indicates fast cooling during the late Early Cretaceous. These data suggest <1–2 km exhumation has occurred in Chinese Altai since the Paleocene. Late Cenozoic surface uplift in the Chinese must have been associated with minimal erosion. Abstract: The Chinese Altai Mountains in western China are bound by Cenozoic transpressional strike-slip faults, many of which show Quaternary activity. To better understand how Mesozoic–Cenozoic deformation has affected the history of exhumation and uplift of the Chinese Altai Mountains, we collected Paleozoic granitoid samples for apatite fission track and apatite U-Th-Sm/He thermochronology. Central apatite fission track ages for N  = 6 samples range from 68 to 104 Ma, whereas apatite U-Th-Sm/He ages range from 56 to 272 Ma for N  = 23 samples ( n  = 80 individual analyses) across four transects in the western Chinese Altai. Our results indicate fast cooling during the late Early Cretaceous followed by slow cooling since. Thermal modeling results suggests < 2 km exhumation has occurred over most of the Chinese Altai since the Paleocene. If significant late Cenozoic surface uplift occurred in the Altai Mountains, as has been proposed, it must have been associated with minimal erosional exhumation. We suggest that the relief of the Chinese Altai largely developed during the late Mesozoic and denudation since has been minimal because of semi-arid climate conditions.